Numerical study of cavitator angle effect on ventilated supercavitating flow - Van-Duyen Pham; Byoung-Kwon Ahn; Cheolsoo Park; Gun-Do Kim; Il-Sung Moon (Engineering Applications of Computational Fluid Mechanics, 2023)
ABSTRACTDespite decades of rigorous research into supercavitating flow, there is still a lack of in-depth knowledge on the properties of ventilated supercavitation with cavitators of varying angle of attack. To address this gap, this study aimed to investigate numerically the supercavity profile, internal pressure behavior, and gas leakage mechanism taking into account the effects of cavitator angle of attack. The study examined five different types of cavitator: 45°, 60°, 90°, 135° cone-shaped and disk-shaped cavitators, all with the same diameter, and evaluated them at seven attack angles (−15°, −10°, −5°, 0°, +5°, +10°, +15°). The results show that, although the maximum diameter of the supercavity remained mostly stable, changes in the cavitator’s angle of attack had a considerable effect on the length and deformation of the supercavity profile. The gas leakage mechanism typically exhibited twin-vortex and quad-vortex tubes. As the cavitator angle of attack increased, the height and distance of these tubes changed significantly, but the pressure distribution inside the cavity remained stable. The findings of this study provide useful information for minimizing supercavity deformation, which can reduce the planning effects resulting from surface–fluid interaction and ultimately enhance the stability and manoeuverability of supercavitating objects.